2002
DOI: 10.1023/a:1023646432427
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Norwalk-like virus (NLV) Outbreaks Occurring in Kyushu Japan between 1988 and 1993

Abstract: In nine outbreaks that occurred in the Kyushu district between 1988 and 1993, we determined the nucleotide sequences of Norwalk-like virus (NLV) gene fragments amplified by RT-PCR and molecular-epidemiologically analyzed the NLV epidemics. It is known that the NLV strains isolated from nine outbreaks of acute gastroenteritis, were divided into five clusters consisting of two genogroups. Described by the year of outbreaks, the genogroup-1 (Norwalk-like virus group) was prevalent in 1988, 1989, and 1992, the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The illness is usually mild and self-limiting, but the virus is highly infectious and often transmitted from person to person in hospitals, hotels, schools, cruise ship, and restaurants [Vinje and Koopmans, 1996;Holtby et al, 2001;Billgren et al, 2002;Love et al, 2002;Marks et al, 2003]. Global outbreaks of gastroenteritis have been caused by plural strains of genogroups I and II [Noel et al, 1997;Otsu et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…The illness is usually mild and self-limiting, but the virus is highly infectious and often transmitted from person to person in hospitals, hotels, schools, cruise ship, and restaurants [Vinje and Koopmans, 1996;Holtby et al, 2001;Billgren et al, 2002;Love et al, 2002;Marks et al, 2003]. Global outbreaks of gastroenteritis have been caused by plural strains of genogroups I and II [Noel et al, 1997;Otsu et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…The GII Lordsdale genotype (GII/4) has been predominant since 1996, and the GII Mexico genotype (GII/3) suddenly appeared and spread during the 1999-2000 season in Osaka City, Japan (11). In another study, various genotypes of NVs were found in Kyushu, Japan, from 1988 to 1993, and the GII Mexico genotype was dominant in 1989 (26). In Japan, raw oysters are the primary source of transmission in small outbreaks, whereas school lunches and catered meals, banquet halls, and hospitals are most often implicated as the vehicles and settings of transmission in large outbreaks (those involving Ͼ50 patients) (10).…”
mentioning
confidence: 96%